2013
DOI: 10.4012/dmj.2012-329
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different adhesives combined with two resin composite cements on shear bond strength to polymeric CAD/CAM materials

Abstract: This study tested the impact of different adhesives and resin composite cements on shear bond strength (SBS) to polymethyl methacrylate (PMMA)-and composite-based CAD/CAM materials. SBS specimens were fabricated and divided into five main groups (n=30/group) subject to conditioning: 1. Monobond Plus/Heliobond (MH), 2. Visio.link (VL), 3. Ambarino P60 (AM), 4. exp. VP connect (VP), and 5. no conditioning-control group (CG). All cemented specimens using a. Clearfil SA Cement and b. Variolink II were stored in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
80
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 31 publications
4
80
2
Order By: Relevance
“…Stawarczyk et al [21] showed that the bond strength between air-abraded PMMA-based polymer and a hybrid composite was not further increased by adhesive conditioning. In contrast, another study demonstrated that without further conditioning no adhesion between air-abraded CAD/CAM polymers and resin composite cements could be achieved [19,21].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Stawarczyk et al [21] showed that the bond strength between air-abraded PMMA-based polymer and a hybrid composite was not further increased by adhesive conditioning. In contrast, another study demonstrated that without further conditioning no adhesion between air-abraded CAD/CAM polymers and resin composite cements could be achieved [19,21].…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, thermocycling might lead to mechanical stress on the bonding area of the repaired substrate. However, it is also discussed that thermocycling might increase the repair bond strength by intensifying the process of post-polymerisation between polymeric CAD/CAM materials and adhesive resins [19].…”
Section: Discussionmentioning
confidence: 99%
“…The various hybrid ceramics produced by different companies all exhibit unique features, since each material has a different composition of ceramic and resin matrix, and the bonding protocol may differ. Bahr et al 7) reported that because the CAD-CAM composite block polymerized in an industrial environment has a very high polymerization rate, inappropriate surface pretreatment will result in a very low bonding strength.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, previous studies have shown that with surface pretreatment by airborne-particle abrasion and adhesive system application, the achievement of adequate bond strength to other methacrylates is possible. [9][10][11][12] Polyetheretherketone (PEEK), in contrast, represents a methacrylate-free, high-performance thermoplastic polymer consisting of aromatic benzene molecules, which are connected alternately by functional ether or ketone groups. 13 It shows good dimensional stability 14 and is radiolucent, making it compatible with imaging techniques such as computed tomography, magnetic resonance imaging, and xray.…”
Section: Clinical Implications Introductionmentioning
confidence: 99%